2010
DOI: 10.1186/1756-0500-3-328
|View full text |Cite
|
Sign up to set email alerts
|

Use of RNAlater in fluorescence-activated cell sorting (FACS) reduces the fluorescence from GFP but not from DsRed

Abstract: BackgroundFlow cytometry utilizes signals from fluorescent markers to separate targeted cell populations for gene expression studies. However, the stress of the FACS process could change normal gene expression profiles. RNAlater could be used to stop such changes in original gene expression profiles through its ability to denature RNase and other proteins. The normal conformational structure of fluorescent proteins must be maintained in order to fluoresce. Whether or not RNAlater would affect signals from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…2.5a). Furthermore, in contrast to a recently published report (Zaitoun et al, 2010), RNAlater did not seem to interfere with GFP fluorescence (Fig. 2.5c).…”
Section: Transcriptome Fixationcontrasting
confidence: 99%
“…2.5a). Furthermore, in contrast to a recently published report (Zaitoun et al, 2010), RNAlater did not seem to interfere with GFP fluorescence (Fig. 2.5c).…”
Section: Transcriptome Fixationcontrasting
confidence: 99%
“…At 69 h detached cells (DC) were collected from the culture medium supernatant. To preserve RNA integrity during FACS sorting of infected cells, cells were treated with RNAlater (27,28). In addition, sporozoite samples were generated by processing infected salivary glands of mosquitoes at day 20 post feeding.…”
Section: Resultsmentioning
confidence: 99%
“…The pellet was loosened by flicking and the cells were resuspended with 250ul of RNAlater and stored at 4°C till all time points were harvested. It has been reported that RFP in contrast to GFP is preserved in RNAlater treated cells (28).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were then spun down at 37 °C, 300g for 10 minutes and resuspended in 1 ml PBS + 2% FCS and placed on ice until FACS. RNAlater was used shortly after sorting, as this reagent leads to decreased GFP expression 49 . To control for gene expression changes that may be induced by FACS, only sorted samples were used in comparative analyses.…”
Section: Methodsmentioning
confidence: 99%